Prekarianizm w Polsce – skala zjawiska, skutki i perspektywy - Jarecki, Wojciech (Annales. Etyka w Życiu Gospodarczym, 2014)
The precariat is a notion and a phenomenon that has drawn special attention of economists since the turn of 20th and 21st centuries. The article is based on the assumption that the precariat involves unwanted and long-term insecurity and uncertainty, a highly changeable situation on the labour market and many other negative consequences. The paper advances the thesis according to which the phenomenon in ques-tion will escalate and be experienced by a growing number of people who have reached pre-retirement age and are no longer mobile in occupational terms. The article is aimed at presenting reasons of possible growth of the problem under discussion, as well as the consequences faced by people who deal with it. Last but not least, potential ways of fighting precarity will be discussed. The analysis will be based on the literature on the subject, data derived from Central Statistical Office of Poland (GUS) and Eurostat, as well as research con-ducted by the author.